Large-Scale Malware Classification Using Random Projections and Neural Networks - Dahl, George; Stokes, Jay; Deng, Li; Yu, Dong (Proceedings IEEE Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2013)
Automatically generated malware is a significant problem for computer users. Analysts are able to manually investigate a small number of unknown files, but the best large-scale defense for detecting malware is automated malware classification. Malware classifiers often use sparse binary features, and the number of potential features can be on the order of tens or hundreds of millions. Feature selection reduces the number of features to a manageable number for training simpler algorithms such as logistic regression, but this number is still too large for more complex algorithms such as neural networks. To overcome this problem, we used random projections to further reduce the dimensionality of the original input space. Using this architecture, we train several very large-scale neural network systems with over 2.6 million labeled samples thereby achieving classification results with a two-class error rate of 0.49% for a single neural networkand 0.42% for an ensemble of neural networks.